2009
DOI: 10.1080/02713680802579196
|View full text |Cite
|
Sign up to set email alerts
|

Pitavastatin Attenuates Leukocyte-Endothelial Interactions Induced by Ischemia-Reperfusion Injury in the Rat Retina

Abstract: Pitavastatin effectively attenuated ischemia-induced leukocyte-endothelial interactions in the rat retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…In many reports on experimental19 20 and clinical populations, pitavastatin improved endothelial function through upregulated endothelial nitric oxide synthase activity. In addition, data from previous reports support the suggestion that pitavastatin treatment reduces the levels of cytokines and chemokines 5 21 22. The relatively quick pleiotropic action of pitavastatin seen in this study is also consistent with observations from a previous study, in which a 2-week course of pitavastatin resulted in improved FMD in patients with hypercholesterolaemia 21 23 24.…”
Section: Discussionsupporting
confidence: 91%
“…In many reports on experimental19 20 and clinical populations, pitavastatin improved endothelial function through upregulated endothelial nitric oxide synthase activity. In addition, data from previous reports support the suggestion that pitavastatin treatment reduces the levels of cytokines and chemokines 5 21 22. The relatively quick pleiotropic action of pitavastatin seen in this study is also consistent with observations from a previous study, in which a 2-week course of pitavastatin resulted in improved FMD in patients with hypercholesterolaemia 21 23 24.…”
Section: Discussionsupporting
confidence: 91%
“…1,2,11,23 On the other hand, pitavastatin attenuated oxidative stress and TBARS, which could be due to the suppression of IKK/NF-kB, thereby reduced ROS production and/or amplification of myocardial antioxidant defense system such as CAT, SOD, GSH, and GSHPx in ischemic-reperfused heart, which scavenges ROS and lipid peroxyl radicals, and prevents myocardial damage. 1,2,[6][7][8][9]21 In this study, we observed a significant downregulation of activated phosphorylated forms of Akt and e-NOS in ischemic-reperfused heart, which were upregulated by pitavastatin treatment. It is well established that NO is a key regulator of myocardial function under physiological conditions, 24,25 and its production is regulated by e-NOS activation, which is mainly arbitrated through a phosphorylation-dependent mechanism involving the serine/threonine kinase pAkt.…”
Section: Discussionmentioning
confidence: 75%
“…10,11 We speculated that the enhanced expression of pAkt, (p) e-NOS and suppression of TNF-a, IKK/NF-kB by pitavastatin negatively regulate the dysregulated production of Bcl-2, Bax, and caspase-3 proteins and attenuates the stimulus-dependent activation of apoptosis and myocytes damage in response to IR. [7][8][9] In our study, to ensure that pitavastatin prevents the myocardial damage caused by IR, serum CK-MB and myocardial (2): absence of any myonecrosis, edema, and inflammation; score (+): focal areas of myonecrosis, edema, and inflammation; score (++): patchy areas of myonecrosis, edema, and inflammation; score (+++): confluent areas of myonecrosis, edema, and inflammation; score (++++): massive areas of myonecrosis, edema, and inflammation. LDH levels were assessed.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the basis of the results of these experiments, many investigators have studied various agents that can attenuate tissue damage by suppressing leukocyte-endothelial interactions in the postischemic retina. Antithrombin III [83,84], tacrolimus (FK506) [85], argatroban (direct thrombin inhibitor) [86], statin [87,88], Rho-associated protein kinase inhibitor [89], superoxide dismutase [90], thalidomide [91], selectin ligands/inhibitor (SKK-60060) [92], triamcinolone acetonide [93], ischemic preconditioning [94,95], platelet depression [81], and 17β-estradiol [96] are reported to reduce leukocyte accumulation in the postischemic retina and thereby reduce neural damage.…”
Section: Leukocyte-endothelial Interactions In Pathological Conditionsmentioning
confidence: 99%